Associação entre citocinas plasmáticas e doença ativa, parâmetros clínicos e laboratoriais de gravidade e coinfecção com HIV na leishmaniose visceral humana - Ricardo Luiz Fontes Moreira (2014)
Visceral leishmaniasis is one of the most severe neglected tropical diseases and fatal if left untreated. Risk factors for death and immunopathogenesis of VL are still not fully elucidated. Thus, in this study plasma cytokines were evaluated during active disease and after VL treatment, as well as their association with HIV co-infection, and clinical and laboratorial parameters of disease severity or death. Plasma levels of IL-2, IL-4, IL-6, IL-10, IL-17A, TNF and IFN-gamma were measured by flow cytometry, in VL patients before and after treatment. Active VL patients showed higher IL-2, IL-4 and IL-10 plasma concentrations as compared to VL patients after specific therapy. HIV co-infected patients showed lower levels of IL-10 as compared to patients with VL without HIV, in univariate analysis. Lower levels of IFN-gamma were found in patients who had bleeding episodes and it was also slightly lower in those who died, in univariated analysis, showing its possible association with disease severity. Occurrence of jaundice was associated with high IL-10. There were negative correlation between hemoglobin levels and leukocyte numbers with plasma IL-2 and IL-6. Positive association between leukocyte numbers with IL-10 were also found. Therefore, these findings highlight the importance of IL-2, IL-4 and IL-10 during active VL, the association between HIV co-infection and low IL-10 levels and the possible role of cytokines in the complex mechanisms involved in clinical and laboratorial findings in VL patients.